TEACHER EDUCATION IN EARLY CHILDHOOD CARE AND EDUCATION: ISSUES AND CONCERNS - Abraham, Jessy (THE PRIMARY TEACHER, 2011)
The staff running the ECCE programmeme is the single most important factor in determining the quality of the programme, yet is the most neglected aspect of the programme. Teacher in the ECCE context is the person who takes care of the education rather than the care component, and as care and education are integral part of ECCE, the training for the teachers at this level requires a perspective different from that of the teacher education addressing elementary and secondary level of schooling. The ECCE teacher education operates in various modes from certificate courses of a few weeks duration to bachelor and post graduate degree levels. As we are gearing up to meet the increased demands of the ECCE teachers due to the implementation of Right to Education Act, we need more programmes in ECCE at degree level to fulfil the objective of providing quality ECCE programmes which support the formal system of education by preparing children in a genuine manner. This paper also substantiates that there is research evidence that the degree level teacher education of ECCE has a positive impact on ECCE outcomes